The struggle over law in Europe - Sandulli, Aldo, 1966- (Abingdon, Oxon [UK] ; New York, NY : Routledge, 2024)
"This book interrogates the role of law in Europe at a time when economic policies have become dominant not only on this continent but globally. Can law be seen as a mere infrastructure? Or does it contribute to defining the social and legal order through its own inherent rules? If the second hypothesis is true, what might these rules be, and how may they be identified? Lastly, to what extent can agreeing a definition of the role of law affect the future of Europe? With the Next Generation European Union, the EU has introduced an unprecedented investment plan for economic recovery and resilience. In doing so, it has become the most important financial intermediary on the continent. But is this simply the prelude to a European economic and financial revival, or does it also aim to strengthen the European legal order in social, political, and constitutional terms? This book argues that the role of law in Europe should aim to achieve a balanced relationship between freedom and solidarity; encouraging economic competition, but also social cohesion. Analysing the role of law in the project of European integration, it maintains that law should be more than an infrastructure for finance and economics, showing how it can act as a guide and a binding force to achieve a more balanced relationship between economics, politics, and law. This book will be of interest to scholars in the fields of public law, European law, law and economics, the philosophy of law, legal history, political theory, and political science, as well as others concerned with the future of European integration"--
The prismatic construction of the European legal order -- The relationship between European law, economics, and finance -- Technical expertise and democratic legitimacy in European law over the last quarter century -- The ability of administrative law to adapt and expand as the European legal oder takes shape -- The science of administrative law and the role of the jurist in the construction of the European legal system -- The law in the new European legal order.
Keywords: Administrative law -- European Union countries; Law -- European Union countries; LAW / Public